New insights into sinusoidal obstruction syndrome. Issue 10 (9th October 2017) - Piccin, Andrea; Sartori, Maria T.; Bisogno, Gianni; Van Schilfgaarde, Muriel; Saggiorato, Graziella; Pierro, Angela M. D.; Corvetta, Daisy; Marcheselli, Luigi; Mega, Andrea; Gastl, Günther; Cesaro, Simone
Abstract: Background: Entry criteria included patients who developed sinusoidal obstruction syndrome (SOS) at a single centre from January 2000 to December 2011. Patients who underwent haemopoietic stem cell transplantation or actinomicyn‐based chemotherapy for nephroblastoma were selected. The study group comprised five patients with SOS who were compared with a control group of seven patients without SOS. Aim: To study the relationships between endothelial extracellular vesicles (EV) and plasminogen‐activator inhibitor type 1(PAI‐1) to assess their modification in the early phase of SOS. Methods: Consecutive blood samples were tested for cell‐derived EV, PAI‐1 and coagulation parameters. Any statistically significant correlation between all datasets was searched. Results: Antithrombin level and platelet count were statistically significantly reduced in SOS patients, suggesting a consumption status. PAI‐1:Ag and PAI‐1:act showed an inverse relationship with platelet counts (coef. −0.034, SE = 0.016; P  = 0.041 and −0.052, SE = 0.019; P  = 0.011 respectively). During follow up, PAI‐1:Ag was inversely related to EV CD144+ (coef. −0.261, SE = 0.094; P  = 0.007) and antithrombin (coef −0.509, SE = 0.175; P  = 0.005). PAI‐1:act showed an inverse association with EV CD144+ (coef.−0.251, SE = 0.121; P  = 0.043), EV CD31+/CD41+ (coef. −0.004, SE = 0.002; P  = 0.026) and antithrombin (coef. −0.470, SE = 0.220; P  = 0.038). EV generated by rupture of gap junctions (EV CD144+) were increased in SOS patients and also showed a change over time. Conclusion: This study demonstrates the existence of an ongoing procoagulant and hypofibrinolytic status in SOS, indicating a possible role for anticoagulant therapy. Moreover, these findings suggest a role for EV CD 144+, either alone or in combination with PAI‐1, as a new biomarker for SOS.